Differential Net Migration Rate and the Quality of Life: A Reply with Additional Evidence - Liu, Ben-chieh (The Review of Economics and Statistics, 1980)
conditioned and the nine slope coefficients (B-values) estimated by the stepwise procedure are, in fact, correlated. In summary, we conclude that, due to intercorrelation among the nine input categories, the true role of economic motivation in the decision to relocateparticularly for nonwhites-is still an open issue. Our tests indicate that the explanatory power of the Liu Overall Index in this regard is, at best, misleading.